The role of big data management to enhance business performance - Azlina Othman; Safawi Abdul Rahman (International Business Information Management Association, IBIMA, 2024)
Big data is a universal phenomenon nowadays. as large amount of data comes from various sources including personalized social media, organizational data, government records, business transaction and etc. To some extent, big data represents a paradigm shift in the ways we study and understand the world. At a very least, it is seen as a way to better utilize and creatively analyze fine grained data for individual and organizational benefit. However, some business organization are not properly cope with the shift of the paradigm and appreciate the art of management triggered by the big data phenomena. Therefore, drawing on a systematic review from literature, this paper presents a discussion on the roles of big data management to create positive outcome which can support a business organization to enhances their performance. The way big data management roles to create positive outcome and enhance a business organization was discovered and clearly discuss in this paper as a result of systematic review.